Balance Nutrition Education Through Recipe Books in an Effort to Prevent Wasting in the Work Area of Pardasuka Health Center - Erika Damayanti; Harris Rambey; Rismawati Hutapea; Annisa Kusumawardani; Iis Sulastri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Wasting is an acute nutritional problem among children under five that remains a public health challenge in Pringsewu Regency, with a prevalence reaching 11.1%. One of the primary risk factors for this condition is the low knowledge of mothers regarding the principles of balanced nutrition and variations in processing local food. This community service activity (PkM) aims to improve the knowledge of mothers with children under five regarding balanced nutrition through education based on the